Cyberterrorism : the rise of misinformation and disinformation - Das, Ravindra (CRC Press, 2025)
"The world today is becoming more interconnected than ever before. Because of this, the spread of Misinformation and Disinformation is literally like wildfire, especially with the use of the social media platforms. In this book, we cover this topic in great detail. By focusing on the following: What Misinformation and Disinformation is all about. The role of Generative AI in Misinformation and Disinformation. The role of Social Engineering in Misinformation and Disinformation. The role of Cyberbullying in Misinformation and Disinformation. Tools to mitigate Misinformation and Disinformation. This will for sure be an explosive topic in the coming years for Cybersecurity"-- Provided by publisher.
Keywords: Misinformation.; Disinformation.; Computer security.; elektronické knihy; electronic books